2013
DOI: 10.1039/c3sm50301a
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–surfactant complexation as a generic route to responsive viscoelastic nanoemulsions

Abstract: We present a new scheme for imparting thermoreversible viscoelasticity to oil-in-water nanoemulsions based on polymer-surfactant self-assembly in solution. Specifically, bridging of polymer-induced micelles in the aqueous phase give rise to a transient network of interdroplet bridges without compromising colloidal stability. Characterization of the structure, dynamics, and rheological properties over a broad range of material chemistries and compositions suggests rules for controlling the resulting viscoelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 71 publications
2
50
0
Order By: Relevance
“…However, in previous work, Kim et al established that these nanoemulsions also form low-temperature viscoelastic phases due to the formation of temporary networks mediated by interdroplet bridging of polymersurfactant complexes in solution. 26 Although it was found that the droplets remained colloidally stable in such cases, SANS measurements exhibited increased low-q scattering rather than a low-q plateau expected for well-dispersed droplets. Thus, the clusters apparent in cryo-TEM at low temperatures could be dynamic manifestations of this temporary network.…”
Section: Cryo-temmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in previous work, Kim et al established that these nanoemulsions also form low-temperature viscoelastic phases due to the formation of temporary networks mediated by interdroplet bridging of polymersurfactant complexes in solution. 26 Although it was found that the droplets remained colloidally stable in such cases, SANS measurements exhibited increased low-q scattering rather than a low-q plateau expected for well-dispersed droplets. Thus, the clusters apparent in cryo-TEM at low temperatures could be dynamic manifestations of this temporary network.…”
Section: Cryo-temmentioning
confidence: 99%
“…The large exponents could be due to the complex nature of our nanoemulsions. For example, polymer-droplet interactions may contribute signicantly to the viscoelasticity of the aggregated droplet network, 26 and such contributions would be exacerbated at low f due to reduced droplet-droplet interactions within the percolated droplet network. Nevertheless, the precise origin of these anomalously large exponents warrants further study beyond the scope of this work.…”
Section: 49mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we developed a model system of non-aggregating, viscoelastic Brownian suspensions in polymer solutions in which such studies can be made [23]. The colloidal fluid is comprised of oil-in-water nanoemulsions in the presence of polyethylene glycol (PEG) and sodium dodecyl sulfate (SDS).…”
Section: Peclet Numbermentioning
confidence: 99%
“…Recalling that PEGDA and photoinitiator have no qualitative effect on the observed droplet morphology prior to UV exposure, this result indicates that the sequestration of PEGDA to a thin (4−6 nm) water film suppresses its ability to form a percolated polymer network. Several potential explanations for this include the possibility that (i) the reactivity of either the photoinitiator or polymerizing acrylic groups is suppressed at the oil−water interface (e.g., due to the presence of oxygen in the cyclohexane phase), which forms a nonreactive boundary layer comparable to the water film thickness; 40 (ii) interactions between PEGDA and the surfactants or the cyclohexane−water interface result in interfacial adsorption of acrylic groups, 41 inhibiting their polymerization upon UV exposure; (iii) the spatial confinement of PEGDA within the thin water shell prevents the formation of a mechanically robust polymeric network. Confirming which of these possible mechanisms is operative in the present experiments would require direct observation of the reactive species and/or PEGDA conformation within the water film during reaction and is left for future studies.…”
mentioning
confidence: 99%